Updated BTS Adult Bronchiectasis Guideline 2018: a multidisciplinary approach to comprehensive care. Issue 1 (13th December 2018) - Hill, Adam T; Welham, Sally A; Sullivan, Anita L; Loebinger, Michael R
Abstract : The new British Thoracic Society (BTS) Guideline for Bronchiectasis in Adults has been published. This article provides a summary of key highlights of the new BTS Guideline and covers who to investigate, what investigations should be carried out and a management strategy.